Filantropi Pendidikan Islam Dalam Peningkatan Motivasi dan Prestasi Siswa di Pondok Pesantren Al-Hikmah Gunung Kidul - Kholifah, Siti (Universitas Muhammadiyah Magelang, 2019)
This study aims to determine the type of educational scholarships from philanthropic funds in Al-Hikmah Islamic boarding school, the motivation of Al-Hikmah Islamic boarding school students who donated from philanthropic funds, and to determine the achievements of Al-Hikmah Islamic Boarding School donated from philanthropic funds . This research is in the form of qualitative research and uses a quantitative descriptive approach, while the collection of data using techniques, questionnaires, observations, interviews, and documentation. The conclusion of this study is the education philanthropy fund Al-Hikmah Islamic boarding school was obtained from several aspects including; permanent donors, non-permanent donors, government agencies, syahriyyah wali santri, infaq and community sadaqoh. Islamic education philanthropy at Al-Hikmah Islamic boarding school gives a